STEAM Against Early Childhood Art at PAUD IT INSAN CENDEKIA BANJARSARI SURAKARTA (Texas Journal of Multidisciplinary Studies, 2023)
PAUD Insan Cendekia uses the STEAM method, which in learning at PAUD Insan Cendikia uses the Music and Body Exercise Center in the Foothold When Playing in Music and Body Exercise. After students move their bodies sufficiently with the developmental aspects they have achieved, they enter music games, where they are introduced to various kinds of musical instruments, for example, mini tambourines, mini jimbes, maracas, xylophones, and angklung. Students are invited to play simple music and follow the beats given by the teacher.The focus of this research is how the STEAM learning process in art learning is carried out by the teacher. In this study, using a qualitative descriptive methodology, by collecting data through observation techniques, interviews, and documentation. Data analysis techniques in this study were carried out by collecting data, reducing data, presenting data, and drawing conclusions. The art learning process using STEAM makes students more interested and creative because the musical instruments they play use items from the surrounding environment that will later be made into musical instruments, and students are very happy about this. Teachers and students always synergize when conducting learning in class. Students are invited to sing, and then the teacher explains briefly the meaning or moral message contained in the song. Then I asked my children to sing the song again. To instill character values in students at PAUD IT Insan Cendekia Surakarta, namely by setting an example and getting into the habit of doing good things.